Editorial: Equity and viability of development - El Director (2009)
If we were to find a common thread in these apparently scattered articles, the impact of the economic growth experienced by the country during most of the decade that is coming to an end would come to light; the authors want to feel this process and take pains to show the risks it poses to equity and the very viability of development. In the international recessionary crisis, which seems to have subsided but has certainly not been overcome, it is urgent to draw lessons from the previous period in order to take advantage of these new circumstances to redesign current policies.